The effects of altitude training on hormonal response in professional cyclists - Raphael Faiss; Bastien Krumm; Basile Moreillon; Lena Mettraux; Julian Wackernell; James Spragg; Martin Faulhaber (Current Issues in Sport Science)
Introduction